TUMOR MARKERS - Ibragimova Nadiya Sabirovna; Isakulova Muhabbat Mardanovna; Tursunov Feruz Uktamovich; Aslamova Kumushbonu Jalil qizi (TADQIQOTLAR.UZ, 2024)
Annotation. In order to assess the effectiveness of treatment, identify residual and recurrent tumors, diagnose and predict the tumor process, the article presents data on  the  immunodiagnosis  of  tumors  using  tumor  markers.  A  special  place  in  the diagnosis of tumors is occupied by the determination of the increase in blood serum of tumor  markers,  the  increase  of  which  in  the  blood  serum  is  associated  with  the development of tumor processes of various origins. The main methods that determine the level of tumor markers in peripheral blood are enzyme-linked immunosorbent and chemiluminescent immunoassays.